2021
DOI: 10.1186/s41983-021-00362-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of anxiety and depression among hospitalized COVID-19 patients in Thailand during the first wave of the pandemic: a cross-sectional study

Abstract: Anxiety and depression in hospitalized COVID-19 patients in Thailand during the first wave of the pandemic were investigated. Thai version of Hospital Anxiety and Depression Scale (HADS) was chosen as an instrument for evaluation. Thirty-two voluntary participants completed the questionnaire. Three (9.4%) respondents had abnormal anxiety sub-scale scores while no respondents had abnormal depression sub-scale scores. There was no statistical demographic difference between the anxiety and non-anxiety groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The COVID-19 pandemic exacerbated the depression epidemic in an already overwhelmed health system. Thaweerat, Pongpirul and Prasithsirikul ( 2021 :20) also reported a significant prevalence of anxiety and depression in hospitalised COVID-19 patients, especially during peak periods of each wave. Shader ( 2020 :962) expressed concerns regarding preventing a global COVID-19 depression, acknowledging the potential for a depression epidemic amid an already strained health system.…”
Section: Discussionmentioning
confidence: 92%
“…The COVID-19 pandemic exacerbated the depression epidemic in an already overwhelmed health system. Thaweerat, Pongpirul and Prasithsirikul ( 2021 :20) also reported a significant prevalence of anxiety and depression in hospitalised COVID-19 patients, especially during peak periods of each wave. Shader ( 2020 :962) expressed concerns regarding preventing a global COVID-19 depression, acknowledging the potential for a depression epidemic amid an already strained health system.…”
Section: Discussionmentioning
confidence: 92%
“…Although these figures seem to be different, it's much higher prevalence which were estimated in the community (anxiety 3.8% and depression 3.4%). (Thaweerat et al, 2021) (Saloni Dattani et al, 2021) About risk factors, we found out that 2 factors were the duration of SARS-CoV 2 infection and anger caused getting this virus. Duration of SARS-CoV 2 infected in anxiety comorbid group was lower.…”
Section: Discussionmentioning
confidence: 98%
“…(Han et al, 2020) During the acute illness, common symptoms among patients admitted to hospital for SARS-CoV-2 included anxiety symptoms (9.4%), depressive symptoms (40%), sleep disturbances (28.8%). (Thaweerat et al, 2021) (Chakrabarti S, 2021) Ju W.K et al realized that clinically meaningful psychological symptoms were found in 18% patients for anxiety, 39% for depression, 30% for insomnia, 9% for suicidal tentative. (Kim et al, 2020) According to the other research being conducted by Ebru Sahan et al, the percentage of significant levels of anxiety and depression were 34.9 and 42%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the Southeast Asian region have investigated the impact of COVID-19 on the mental health of patients. In particular, a study in Thailand during the pandemic's early stages revealed that hospitalized COVID-19 patients exhibited relatively low levels of anxiety and depression, with no discernible differences among demographic groups [ 28 ]. Likewise, the research conducted in Malaysia revealed a relatively low prevalence of anxiety among stable COVID-19 patients hospitalized.…”
Section: Discussionmentioning
confidence: 99%